2020
DOI: 10.1002/ctm2.178
|View full text |Cite
|
Sign up to set email alerts
|

Response of patients with chest tightness variant asthma with routine asthma treatment regimen: A 1‐year multicenter, prospective, real‐world study

Abstract: Dear editor, In 2013, we have reported chest tightness being the only respiratory symptom among 24 asthmatic patients on presentation, 1 and referred to this type of asthma as chest tightness variant asthma (CTVA). Compared with patients with classic asthma (CA) or cough variant asthma (CVA), 2,3 patients with CTVA also presented with eosinophilic airway inflammation. However, whether CTVA has similar response to antiasthma treatment as compared with CA remains unclear. We therefore sought to explore the thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(25 reference statements)
1
9
0
1
Order By: Relevance
“…We also demonstrated that FeNO levels were higher in CVA and classic asthma than those in healthy controls and that FeNO were identified as an independent factor to discriminate CVA and non-CVA (20). Recently, Yan et al evaluated the therapeutic response to standard asthma treatments among 76 patients with CTVA in a 52-week multicenter, prospective study (10). There were no significant improvements in FeNO after 52 weeks compared with the baseline level, while chest tightness was significantly ameliorated among most patients with CTVA after treatment.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We also demonstrated that FeNO levels were higher in CVA and classic asthma than those in healthy controls and that FeNO were identified as an independent factor to discriminate CVA and non-CVA (20). Recently, Yan et al evaluated the therapeutic response to standard asthma treatments among 76 patients with CTVA in a 52-week multicenter, prospective study (10). There were no significant improvements in FeNO after 52 weeks compared with the baseline level, while chest tightness was significantly ameliorated among most patients with CTVA after treatment.…”
Section: Discussionmentioning
confidence: 66%
“…In 2013, Shen et al reported 24 patients with asthma whose sole presenting clinical manifestation was chest tightness and referred to this type of asthma as CTVA (3). As is the case in patients with classic asthma or cough variant asthma (CVA) (8,9), patients with CTVA also presented According to their criteria, the diagnosis of CTVA is made based on the chest pain or tightness being the sole symptom and at least one of the following conditions was met : 1) an increase of > 12% and > 200 mL in FEV1 after inhaling short acting β2 agonist ; 2) airway hyperresponsiveness as evidenced by a positive finding of bronchial provocation test ; 3) a weekly variability in diurnal PEF of greater than 10% ; and 4) a marked clinical improvement in response to β2 agonists, with or without ICS (10). The present case also revealed chest pain as the sole symptom and had medical history of outgrown childhood asthma and allergies to several animals with peripheral blood eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al further found that CTVA was associated with airway inflammation similar to that of typical asthma (22). A one year multicenter, prospective clinical study showed that patients with CTVA obtained efficacy by using the same treatment scheme (including ICS) recommended by the guidelines as typical asthma (12). Occult asthma emphasized people with asymptomatic bronchial hyperresponsiveness are at high risk of asthma (5,23).…”
Section: Discussionmentioning
confidence: 99%
“…Many subsequent studies have found that atypical asthma has a pathobiological basis, namely, eosinophilic inflammation, and airway hyperresponsiveness similar to that of classic asthma (9,10). Inhaled corticosteroids (ICS) or a combination of ICS and long-acting beta-agonists (ICS/LABA) resulted in a good response in patients with these asthma types compared with those with classic asthma (11,12). These studies have aided physicians in understanding atypical asthma, reducing the rate of misdiagnosis and improving treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation